Communication uneven acceptance of and resistance to foreign influences in the connected ancient Mediterranean - Driessen, Jan 1958-; Vanzetti, Alessandro 1964- (PUL, Presses universitaires de Louvain, 2020)
This volume has its origin in a similarly entitled session organised at the 24th Annual Meeting of the European Association of Archaeologists in Barcelona in 2018. The specific aim of both the session and this volume was to measure acceptance of, and resistance to, outside influences within Mediterranean coastal settlements and their immediate hinterlands, with an open time range, but with a particular focus on the processes not reflecting simple commercial routes, but taking place at an intercultural level, in situations of developed connectedness. Following a general discussion of the theoretical and long-lasting facets of the discussion on communication, and of some of the reasons for its unevenness, the contributions in the volume give a wide and stimulating view of the ongoing debate about Mediterranean interaction and communication. The papers' timespan is large: from the Late Neolithic of Crete, in the 5th-4th millennium BCE, to the Macedonian conquest of Thrace, in the 4th century BCE. Most contributions, however, focus on the Middle to Late Bronze Ages, as this is a phase of particularly intense communication, which matches the interests and connections of the editors. The geographic frame extends from the Central Mediterranean to Thrace, Cyprus and the Levant, with an important focus on Crete and Mycenaean Greece. Other papers, more than specific areas, instead discuss the figures of some of the actors of the intra-Mediterranean interregional communication, and the nuances of their roles: warriors and merchants.
Session at the 24th Annual Meeting of the European Association of Archaeologists at Barcelona in 2018 (Seite [1])
Keywords: Küste; Antike; Siedlung; Kulturkontakt; Mittelmeerraum; Konferenzschrift -- European Association of Archaeologists -- 2018 -- Barcelona